A review of minimal and defined media for growth of Listeria monocytogenes. (August 2016) - Jarvis, Nathan A.; O'Bryan, Corliss A.; Ricke, Steven C.; Johnson, Michael G.; Crandall, Philip G.
Abstract: Listeria monocytogenes is known to be an important foodborne pathogen and is the causative agent of one of the deadliest foodborne illnesses. The organism has a wide range of environmental conditions under which it will survive and grow, and often contaminates processing plants and retail environments in which ready-to-eat foods are manufactured, prepared and served. Although L. monocytogenes is not a fastidious organism and can grow in a variety of rich media, defined and minimal media are necessary to elucidate the minimal environmental nutrients that are required for the survival and growth of this organism. In addition, many of the virulence factors required for L. monocytogenes to invade and multiply in mammalian host cells are not produced in rich media and thus induction of these factors is best studied in a minimal medium. This review covers the historical development of minimal media for Listeria spp. and explores the various factors required for survival and growth of this organism. To the best of our knowledge, this is the first time that these media have been compared side by side. In order to better compare studies using different chemical substrates such as a different carbon source, all concentrations of components in each medium have been converted to molar concentrations. Highlights: Listeria monocytogenes contaminates areas in which ready-to-eat foods are prepared. L. monocytogenes grows in a wide range of environmental conditions. Many required virulence factors for L. monocytogenes are not produced in rich media. We review the development of minimal media for Listeria spp. side by side.